Alterações no número de cópias genômicas em carcinomas de mama - Tavares, Ana Carolina Tomaz [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Breast cancer (BC) is a heterogeneous both at molecular and clinical level. Patients with similar clinical and histopathological findings can present different prognosis. Analysis of large scale genomic changes have helped to identify regions and genes associated with the various stages of mammary tumorigenesis. The present study aimed to evaluate the genomic profile by Comparative Genomic Hybridization array-based (aCGH), using the platform 4x180K (Agilent Technologies) in 53 primary invasive ductal carcinomas (IDC). The IDC showed 3849 genomic alterations, with similar proportion of genomic gains and losses (1,622 and 1,731, respectively), 444 alterations were found with high copy number gains (12%) and 52 homozygous losses (1%). We were identified 19 significantly recurrent genomic alterations in more than 20% of tumors. Losses were detected at 1p36.32, 8p23.3, 8p23.1, 8p11.23, 11q25, 14q11.1-q11.2, 16q23.3, 16q24.1 and 18q23, and gains at 1q21.1, 1q21.2, 1q22, 1q32.1, 1q42.3, 1q44, 8q24.21 and 15q11.2. The most frequent alterations were gains at 8q24.21 (36%) and 1q44 (32%), and losses at 8p11.23 (28.3%). Gains in 1q21.1-1q21.2 were associated with negative estrogen receptor (ER-) (P = 0.016) tumors. Loss on 8p23.1 was associated with longer disease-free survival (P = 0.027). Losses on 8p23.3 were associated with HER2 + tumors (P = 0.033) and high level of Ki67 (P = 0.036). Gain at 8q24.21 was associated with lower risk of lymph node involvement (P = 0.0199). Loss at 14q11.1-q11.2 was associated with more aggressive tumor characteristics such as grade III (P = 0.0147), high level of Ki67 (P = 0.0096) and worse clinical outcome, with metastasis development (P = 0.0375). Loss at 18q23 was associated with progesterone receptor negative (PR-) (P = 0.0065) tumors. The comparison of the genomic alterations according to receptor status ER, PR and HER2, lymph node involvement (LN) and development of distant metastases (DM) revealed ...

O câncer de mama (CM) é uma doença heterogênea em relação às alterações moleculares, composição celular e evolução clínica. Pacientes com características clínicas e histopatológicas semelhantes podem apresentar prognósticos distintos. Análises de alterações genômicas em larga escala têm contribuído para identificar regiões e genes associados com os vários estágios da tumorigênese mamária. O presente estudo teve como objetivo avaliar o perfil de alterações no número de cópias genômicas por Hibridação Genômica Comparativa baseada em arrays (aCGH), utilizando a plataforma 4x180K (Agilent Technologies) em 53 carcinomas ductais invasivos (CDI) primários. Os CDI apresentaram 3.849 alterações genômicas, com semelhante proporção de perdas e ganhos genômicos (1.622 e 1.731, respectivamente), 444 ganhos em alto nível (12%) e 52 perdas homozigotas (1%). Foram identificadas 19 alterações genômicas significativamente recorrentes presentes em mais de 20% dos tumores. Foram detectadas perdas em 1p36.32, 8p23.3, 8p23.1, 8p11.23, 11q25, 14q11.1-q11.2, 16q23.3, 16q24.1 e 18q23; e ganhos em 1q21.1, 1q21.2, 1q22, 1q32.1, 1q42.3, 1q44, 8q24.21 e 15q11.2. As alterações mais prevalentes foram ganhos em 8q24.21 (36%) e 1q44 (32%), e a perda em 8p11.23 (28,3%). Ganhos em 1q21.1-1q21.2 foram associados com tumores negativos para o receptor de estrógeno (ER-) (P=0,016). Perda em 8p23.1 foi associada com um maior tempo de sobrevida livre de doença (P=0,027) e perda em 8p23.3 com tumores HER2+ (P= 0,033) e Ki67 alto (P= 0,036). Ganho em 8q24.21 foi associado com menor risco de acometimento de linfonodos (P=0,0199). A perda em 14q11.1-q11.2 associou-se com características de maior agressividade tumoral, como grau III (P=0,0147), Ki67 alto (P=0,0096) e pior evolução clínica, desenvolvimento de metástase (P=0,0375). Perda em 18q23 foi associada com tumores negativos para o receptor de progesterona (PR-) (P=0,0065). A ...
Keywords: Genoma humano; Expressão gênica; Câncer - Prognóstico; Human genome